Controllability and stability of the perturbed Chen chaotic dynamical system - Plienpanich T. (2014)
In this paper, we study perturbed Chen chaotic dynamical system. Firstly, we study the sufficient conditions of parameters which guarantee that the equilibrium points of perturbed Chen chaotic dynamical system are asymptotically stable. Secondly, we study methods for controlling chaos such as feedback control and bounded feedback control that suppress the chaotic behavior to unstable equilibrium points. Finally, we present chaos synchronization of perturbed Chen chaotic dynamical system by using active control and adaptive control. © 2005 Elsevier Inc. All rights reserved.